2007
DOI: 10.1098/rspb.2007.0043
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of frequency-dependent mate choice: keeping up with fashion trends

Abstract: The diversity of sexual traits favoured by females is enormous and, curiously, includes preferences for males with rare or novel phenotypes. We modelled the evolution of a preference for rarity that yielded two surprising results. First, a Fisherian 'sexy son' effect can boost female preferences to a frequency well above that predicted by mutation-selection balance, even if there are significant mortality costs for females. Preferences do not reach fixation, however, as they are subject to frequency-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 49 publications
(68 reference statements)
1
36
0
Order By: Relevance
“…These results suggested that the third alternative acted as a competitive rather than dominated option, because the pattern observed was consistent with the "similarity" rather than with the "attraction effect". Royle et al (2008) explained their results as the effect of the preference for the rare-phenotype (Eakley and Houde, 2004;Kokko et al, 2007), a pattern that has been observed also in other choice contexts (Waite, 2008).…”
Section: Comparative Mate Choice and Rationality In Decision Makingmentioning
confidence: 54%
“…These results suggested that the third alternative acted as a competitive rather than dominated option, because the pattern observed was consistent with the "similarity" rather than with the "attraction effect". Royle et al (2008) explained their results as the effect of the preference for the rare-phenotype (Eakley and Houde, 2004;Kokko et al, 2007), a pattern that has been observed also in other choice contexts (Waite, 2008).…”
Section: Comparative Mate Choice and Rationality In Decision Makingmentioning
confidence: 54%
“…Qvarnström (1999) similarly suggests that indirect benefits of mate choice are reduced in fluctuating or heterogeneous environments (see also Collins et al 1999). On the other hand, Mills et al (2007) suggest that variable environments (density cycles in the context of their study species, the bank vole) can instead help by maintaining alternative genotypes, while Kokko et al (2007) consider a special case-preference for rare male phenotypes-and show how imperfectly expressed female choice can aid preference evolution rather than hinder it because it helps to maintain more variation. Our results reconcile these diverse views, by showing that it is not sufficient to focus on one side of the coin only, i.e.…”
Section: Discussionmentioning
confidence: 96%
“…enormous mutation rates between A and a: this would obviously maintain much variation, but in the extreme (l = m = 0.5 in our model) this simultaneously means that parental genotypes no longer predict what alleles offspring inherit, which again makes mate choice pointless. It is important to realize that the positive and negative effects of variationmaintaining mechanisms generally do not cancel out, instead the net balance can remain either positive or negative (Kokko et al 2007). In the case of male mixing, this balance depends on how much mixing there is.…”
Section: Discussionmentioning
confidence: 98%
“…In the sexual selection literature, this issue underpins the 'lek paradox' [2]. A population under strong sexual selection might be expected to converge on a single 'most attractive' phenotype, but attractive traits often show high additive genetic variance [3]. In understanding the maintenance of genetic variation in attractive traits, it is worth noting that an individual's attractiveness depends not only on their phenotype, but also on the distribution of rivals' phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Males bearing rare colour patterns enjoy greater survivability in the wild [6], and enhanced mating success in both the laboratory [7,8] and wild [9]. Preferences for rare phenotypes can exert negative frequency-dependent selection, a form of selection that prevents the loss of rare alleles, thus maintaining additive genetic variance [3]. Negative frequency-dependent mate choice can arise via a number of mechanisms, including avoiding familiar individuals [10,11], individuals who resemble previous mates [12] or preferring mates with novel or rare sexual signals [8].…”
Section: Introductionmentioning
confidence: 99%